Athen, Griechenland. Kerameikos. Archäologischer Kontext von Fluchtafeln: Brunnen B 34 - Stroszeck, Jutta (e-Forschungsberichte des DAI, 2019)
The recent find of dozens of curse tablets in a well in the Kerameikos excavation puts the whole Athenian cursing habit into perspective: while during the fifth and fourth century BC curse tablets were mainly deposited in tombs, the bulk of finds from the Early Hellenistic periods onwards comes from wells. This is most probably related to the change in the necropoleis caused by the law of Demetrius of Phaleron in 317/307 BC, who also installed an institution to control the law.